Catalytic Efficiency of Carbon-Cementitious Microfiltration Membrane on the Ozonation-Based Oxidation of Small Molecule Organic Compounds and Its Alkaline Buffering Effect in Aqueous Solution - Jingyi Sun; Zhonglin Chen; Shan Liu; Jing Kang; Yuhao Guo; Liming Cai; Jimin Shen; Binyuan Wang; Shengxin Zhao; Zilong Song (Membranes, 2021)
In this study, powdered activated carbon (PAC) was added to replace the silica in a cementitious microfiltration membrane (CM) to solve the problems of the low mechanical strength and short lifetime of CMs. The carbon-cementitious microfiltration membrane (CCM) was fabricated by the dry pressing method and cured at room temperature. The bending strength of CCM was 12.69 MPa, which was about three times more than that of CM. The average pore size was 0.129 μm, and was reduced by about 80% compared to that of CM. The addition of PAC did not reduce the degradation efficiency of membrane catalytic ozonation. Because of the strong alkaline buffering ability of CCM, the CCM–ozone coupling process could eliminate the effect of the pH value of the solution. The strong alkaline environment inside the membrane pores effectively accelerated the ozone decomposition and produced oxidizing radicals, which accelerated the reaction rate and improved the utilization rate of ozone. The CCM–catalytic ozonation reaction of organic compounds occurred within the pores and membrane surface, resulting in the pH of the solution belonging to the neutral range. The addition of PAC accelerated the mass transfer and made the pollutants and oxidant react in the membrane pores and on the membrane surface. The reuse experiments of the CCM–ozone coupling process for removing nitrobenzene demonstrated that CCM has good catalytic activity and reuse stability. It broadens the application scope of CCM in the field of drinking water and provides theoretical support for the practical application of CCM.